School Principal Administrative-Supervisory Leadership During the Pandemic: A Phenomenological Qualitative Study - Francisca T Uy; John Michael Sasan; Osias Kit Kilag (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
This qualitative study aims to explore the administrative-supervisory leadership experiences and perspectives of fifteen (15) school principals in the Division of Toledo City, Cebu, DepEd Region VII, during the COVID-19 pandemic crisis. The research utilized a descriptive phenomenological approach, which involved face-to-face semi-structured interviews, observation notes, and documentation. Thematic analysis was employed to analyze the data in six steps, including familiarization, coding, creating themes, reviewing themes, defining and naming themes, and creating a report. The findings of the study revealed that principals faced various challenges during the pandemic crisis, including maintaining the continuity of learning, ensuring the safety of students and teachers, managing resources, and supporting the well-being of school personnel. Despite these challenges, the principals demonstrated strong leadership skills by adapting to the situation, collaborating with stakeholders, and implementing innovative strategies. The study's limitations include a small sample size and a specific geographic location, which limits the generalizability of the findings. This study contributes to the understanding of how school principals experience and navigate leadership during a crisis, particularly in the context of the COVID-19 pandemic. The practical implications of this study suggest that school leaders should prioritize collaboration and adaptability in crisis management, support the well-being of school personnel, and implement innovative strategies to address challenges. The study's novelty lies in its application of a phenomenological approach to explore the subjective experiences of school principals during the COVID-19 pandemic crisis.